THE INFLUENCE OF CREATIVITY TEACHING TEACHERS ON ECONOMIC LEARNING OUTCOMES MEDIATED CREATIVITY QUOTIENT - Nurhayati, Fanny; Saptono, Ari; Suparno (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
This study aims to determine the effect of teacher teaching creativity and student creativity quotient oneconomic learning outcomes in class X state senior high schools in East Jakarta. This study uses aquantitative method with a correlational approach. The population of this study was 11163 students ofclass X high school in East Jakarta, the sample selection technique used multistage randomsampling, and a sample of 208 students was selected. The data collection for the teacher's teaching creativity and the creativity quotient used a questionnaire, while the learning outcomes usedsecondary data. This study used Path analysis. Results showed that teachers' teaching creativitysignificant influence on student learning outcomes, the creativity quotient insignificant influence onstudent learning outcomes, teacher teaching creativity significant influence on creativity quotient,and teachers' teaching creativity, mediated by creativity quotient, insignificant effect on studentlearning outcomes. The finding of this study implies that the teacher's teaching creativity can increase thecreativity quotient of students and students' learning outcomes of economics.